Beneficial Microorganisms Improve Agricultural Sustainability under Climatic Extremes - Jalal, Arshad [UNESP]; Oliveira, Carlos Eduardo da Silva [UNESP]; Rosa, Poliana Aparecida Leonel [UNESP]; Galindo, Fernando Shintate [UNESP]; Teixeira Filho, Marcelo Carvalho Minhoto [UNESP] (MDPI, 2023)
The challenging alterations in climate in the last decades have had direct and indirect influences on biotic and abiotic stresses that have led to devastating implications on agricultural crop production and food security. Extreme environmental conditions, such as abiotic stresses, offer great opportunities to study the influence of different microorganisms in plant development and agricultural productivity. The focus of this review is to highlight the mechanisms of plant growth-promoting microorganisms (especially bacteria and fungi) adapted to environmental induced stresses such as drought, salinity, heavy metals, flooding, extreme temperatures, and intense light. The present state of knowledge focuses on the potential, prospective, and biotechnological approaches of plant growth-promoting bacteria and fungi to improve plant nutrition, physio-biochemical attributes, and the fitness of plants under environmental stresses. The current review focuses on the importance of the microbial community in improving sustainable crop production under changing climatic scenarios.
Keywords: abiotic stresses; crop productivity; growth-promoting fungi; PGPBs; plant tolerance